Literature Study: Cooperative Learning Model Attention, Relevance, Confidence, and Satisfaction (ARCS) According to John M. Keller : Studi Literatur: Model Pembelajaran Kooperatif Attention, Relevance, Confidence, Satisfaction (ARCS) Menurut John M. Keller - Afidah Nur; Machful Indra Kurniawan (Universitas Muhammadiyah Sidoarjo, 2022)
Learning in elementary schools is still experiencing problems such as teachers who still have difficulty in choosing and implementing innovative learning models. This study aims to describe the concept of the ARCS type cooperative learning model (Attention, Relevance, Confidence, and Satisfaction) according to John M. Keller and to describe the relevance of the ARCS type cooperative learning model in understanding the concepts of elementary school students. This research uses a qualitative descriptive study approach with the type of library research. Sources of data in this study were obtained from books, research journals, and literature books. The analysis technique of this research uses descriptive analysis method. The results of this study indicate that the concept of cooperative learning model is a learning model that is carried out by forming small groups to learn. The ARCS type of cooperative learning model has relevance in improving students' conceptual understanding in all learning competencies in elementary schools, both in learning science or natural sciences (IPA), mathematics, and social sciences (IPS).